Quantification of mid and late evoked sinks in laminar current source density profiles of columns in the primary auditory cortex - Schaefer, Markus K.; Hechavarría, Julio C.; Kössl, Manfred (Frontiers in Neural Circuits, 2015)
Current source density analysis assesses spatiotemporal synaptic activations at somatic and/or dendritic levels in the form of depolarizing current sinks. Whereas many studies have focused on the short (<50 ms) latency sinks, associated with thalamocortical projections, sinks with longer latencies have received less attention. Here we analyzed laminar current source density patterns for the first 600 ms after stimulus onset in the primary auditory cortex of Mongolian gerbils. By applying an algorithm for contour calculation, three distinct mid and four late evoked sinks were identified in layers I, III, Va, VIa, and VIb. Our results further showed that the patterns of intracortical information-flow remained qualitatively similar for low and for high sound pressure level stimuli at the characteristic frequency (CF) as well as for stimuli ± 1 octave from CF. There were, however, differences associated with the strength, vertical extent, onset latency, and duration of the sinks for the four stimulation paradigms used. Stimuli one octave above the most sensitive frequency evoked a new, and quite reliable, sink in layer Va whereas low level stimulation led to the disappearance of the layer VIb sink. These data indicate the presence of input sources specifically activated in response to level and/or frequency parameters. Furthermore, spectral integration above vs. below the characteristic frequency of neurons is asymmetric as illustrated by current source density profiles. These results are important because synaptic feedback associated with mid and late sinks – beginning at 50 ms post stimulus latency – is likely crucial for response modulation resulting from higher order processes like memory, learning or cognitive control.